Teachers' perspective on the Namibian portfolio for languages: three years after implementation (Journal for Studies in Humanities and Social Sciences, 2018)
The Namibian Portfolio for Languages (NPL) was conceived in 2013 by five Namibian educators and dis-tributed to seven Namibian secondary schools to approximately 500 pupils learning French as a foreign language. Since its implementation, the impact of the NPL is researched both on pupils and teachers by the University of Namibia French section, in order to assess its learner-centered pretensions, its formative assessment capacity, and its support in self-assessment. This paper looks into teachers’ feedback on the NPL practicality in and outside the classroom environment after three years of implementation. Further-more, it aims at assessing NPL’s relevance as a tool to the benefit of self-assessment and formative assessment.